DESIGNING A TOURIST GUIDE BOOK FOR GEDONG SONGO TEMPLE IN SEMARANG REGENCY AS A MEDIA FOR TOURIST EDUCATION - Krisnanto, Dimas Bayu (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2019)
Gedong Songo Temple has many benefits in the field of knowledge, especially in the history of Gedong Songo Temple and the meaning of each temple. Given that aside from being a recreational media, it is hoped that Gedong Songo Temple tourism objects can be used as educational media. Later tourists can understand and bring appreciation to the Gedong Songo Temple. But the facts found, there is still a lack of communication media for tourists regarding information about the Gedong Songo Temple. This is evidenced by the limited media of tourists to get information about Gedong Songo Temple. The purpose of this study project is to design a media that is later expected to be able to provide information to tourists about Gedong Songo Temple. The work that will be designed as a tourist education media of Gedong Songo Temple is a media in the form of a guidebook. The book will be designed in the form of a combination of photography, infography, and text containing information about the history and meaning of each temple